The Enigmas of Lymphatic Muscle Cells: Where Do They Come From, How Are They Maintained, and Can They Regenerate? - Kenney, H. M.; Peng, Yue; de Mesy Bentley, Karen L.; Xing, Lianping; Ritchlin, Christopher T.; Schwarz, Edward M. (Current Rheumatology Reviews, 2023)
Lymphatic muscle cell (LMC) contractility and coverage of collecting lymphatic vessels (CLVs) are integral to effective lymphatic drainage and tissue homeostasis. In fact, defects in lymphatic contractility have been identified in various conditions, including rheumatoid arthritis, inflammatory bowel disease, and obesity. However, the fundamental role of LMCs in these pathologic processes is limited, primarily due to the difficulty in directly investigating the enigmatic nature of this poorly characterized cell type. LMCs are a unique cell type that exhibit dual tonic and phasic contractility with hybrid structural features of both vascular smooth muscle cells (VSMCs) and cardiac myocytes. While advances have been made in recent years to better understand the biochemistry and function of LMCs, central questions regarding their origins, investiture into CLVs, and homeostasis remain unanswered. To summarize these discoveries, unexplained experimental results, and critical future directions, here we provide a focused review of current knowledge and open questions related to LMC progenitor cells, recruitment, maintenance, and regeneration. We also highlight the high-priority research goal of identifying LMC-specific genes towards genetic conditional- inducible in vivo gain and loss of function studies. While our interest in LMCs has been focused on understanding lymphatic dysfunction in an arthritic flare, these concepts are integral to the broader field of lymphatic biology, and have important potential for clinical translation through targeted therapeutics to control lymphatic contractility and drainage.
Keywords: contractility